The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0034-89102007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento alimentar em moradia estudantil: um espaço para promoção da saúde

Abstract: OBJECTIVE:To qualitatively describe food practices of students living in a residence hall. METHODS:A quantitative and qualitative study was carried out in a drawn sample of 100 university students living in a residence hall in the city of Campinas, Southeastern Brazil, in 2004. Students were interviewed using a questionnaire to collect 24-hour food recall information including open questions on shopping and intake practices. Criteria were established for the analysis of meal quality. The Chi-square and the exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
47

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 9 publications
3
13
0
47
Order By: Relevance
“…The prevalence of breakfasting was similar to those found by other studies, which varied from 25.2% to 95.0% 4,[6][7][8][9]21,22 . Although skipping breakfast was unusual, it may lead to nutritional deficiencies and increase the intake of energydense foods, favoring the development of diseases 8,10,23 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The prevalence of breakfasting was similar to those found by other studies, which varied from 25.2% to 95.0% 4,[6][7][8][9]21,22 . Although skipping breakfast was unusual, it may lead to nutritional deficiencies and increase the intake of energydense foods, favoring the development of diseases 8,10,23 .…”
Section: Discussionsupporting
confidence: 89%
“…This study selected eleven foods for analysis according to the plausibility reported in the literature 4,5,8 . The consumption of some foods was 100% adequate, so they were excluded from the analysis.…”
Section: E T H O D Smentioning
confidence: 99%
See 2 more Smart Citations
“…No entanto, estudos relatam que transtornos alimentares e comportamento alimentar alterado são prevalentes em grupos específicos, como atletas, estudantes universitários, especialmente da área da saúde [13][14][15][16] , e profissionais que lidam com a corporeidade, dentre eles os nutricionistas e os estudantes do curso de Nutrição 17,18 .…”
Section: Introductionunclassified